Exploring the Scientific Truth of Marriage Dispensation: An Interdisciplinary Study of Islamic Teachings - Yayat Dimyati (Sekolah Tinggi Agama Islam At-Tahdzib, Ngoro, Jombang, Indonesia, 2025)
Background. This scientific paper examines marriage dispensation in Islam through an interdisciplinary approach that combines the perspectives of religion, law, sociology, psychology, and health. Marriage dispensation, as a form of legal exception in early marriage, is often understood narrowly only from the religious normative side. In fact, in the contemporary social and scientific context, this practice has multidimensional implications that require a more holistic analysis. By examining the sharia arguments and the maqashid al-syari'ah framework. Aim. The findings show a gap between the understanding of dogma and scientific reality that should complement each other. Therefore, a contextual reinterpretation of Islamic teachings is needed that takes into account scientific and humanitarian dimensions. This study recommends the integration of revelation and science as a basis for formulating a just and sustainable marriage dispensation policy. Thus, an interdisciplinary approach becomes an important tool in exploring the scientific truth of religious dogma wisely and responsibly. Methods. The research method in the study that you have compiled is an interdisciplinary qualitative approach with a case study strategy and empirical data analysis. The following is a complete description of the interdisciplinary qualitative approach. This study uses a qualitative approach because it aims to understand the meaning, views, and social impacts of the practice of marriage dispensation, not to test hypotheses statistically. This approach is interdisciplinary because it combines perspectives from its purpose is to produce a comprehensive and contextual understanding of the issue of marriage dispensation and this strategy was chosen to examine several concrete cases of marriage dispensation in Indonesia, including data from religious courts and interviews available in reports from official institutions such as UNICEF, National Commission on Violence Against Women, and Indonesian Child Protection Commission. Case studies allow for in-depth analysis of the social and religious dynamics behind the practice. Results. This study recommends the integration of revelation and science as a basis for formulating a just and sustainable marriage dispensation policy. Thus, an interdisciplinary approach becomes an important tool in exploring scientific truth from religious dogma wisely and responsibly.